Analysis of Mechanical, Metallurgical and Fatigue Behavior of Friction Welded AA6061-AA2024 Dissimilar Aluminum Alloys in Optimized Condition. (2018) - Vigneshwar, M.; Selvamani, S.T.; Hariprasath, P.; Palanikumar, K.
Abstract: Dissimilar joints are having greater demands in each and every sectors for reducing the weight of the components with excellent mechanical properties at high temperature and also it possess increased corrosive resistance. Aluminum alloys are widely used in day-to-day applications in which 6xxx series Al alloys are majorly incorporated in automotive industries. The 2xxx series Al alloys offers an increased performance both in static and dynamic conditions due to the presence of copper, chromium, magnesium and iron constituents. In general, 6xxx series alloys undergoes failure with any slight changes in environmental conditions but the 2xxx series Al alloys are having better resistance comparitively. Therefore, in this research work, an attempt was made in order to replace some of the 6xxx series alloys to 2xxx series Al alloys with the help of Friction Welding (FW) process which will enhance the performance of the components. So for, the process parameters were optimized using Response Surface Methodology (RSM) and its effect on the mechanical, metallurgical and fatigue properties were analyzed. Also, the properties of the joints were characterized with the help of advanced facilities such as optical metallurgical microscopy and scanning electron microscopy to understand its surface morphology.